2019
DOI: 10.3390/molecules25010115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Volatile Components in Selaginella doederleinii by Headspace Solid Phase Microextraction-Gas Chromatography-Mass Spectrometry

Abstract: Selaginella doederleinii (SD) is a perennial medicinal herb widely distributed in China. In this study, the volatile components of SD from two regions (24 batches), namely Zhejiang and Guizhou, were determined by combining headspace solid phase microextraction and gas chromatography-mass spectrometry (HS-SPME/GC-MS). After investigating different influence factors, the optimal conditions for extraction were as follows: The sample amount of 1 g, the polydimethylsiloxane-divinylbenzene (PDMS-DVB) fiber of 65 µm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The chemical composition of MEVT and AELN was performed using Trace GC-ISQ mass spectrometer (Thermo Scientific, Austin, TX, USA) with a direct capillary column TG-5MS (30 m × 0.25 mm × 0.25 μm film thickness) as previously described [38,39]. The column oven temperature was initially held at 50°C and then increased by 5°C/min to 250°C withhold 1 min then increased to 300 at the rate of 30°C /min.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
“…The chemical composition of MEVT and AELN was performed using Trace GC-ISQ mass spectrometer (Thermo Scientific, Austin, TX, USA) with a direct capillary column TG-5MS (30 m × 0.25 mm × 0.25 μm film thickness) as previously described [38,39]. The column oven temperature was initially held at 50°C and then increased by 5°C/min to 250°C withhold 1 min then increased to 300 at the rate of 30°C /min.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
“…Shi et al [48] confirmed that osmiophilic matrix particles played a key role in floral formation in a study of Osmanthus fragrans. [49][50][51]. The volatile compounds of many water lily cultivars have been widely studied, and the volatile components differ [29,52].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of MEBV and AERC was performed using Trace GC-ISQ mass spectrometer (Thermo Scientific, Austin, TX, USA) with a direct capillary column TG-5MS (30 m × 0.25 mm × 0.25 µm film thickness) as previously described [48]. The column oven temperature was initially held at 50 • C and then increased by 5 • C /min to 250 • C withhold 1 min then increased to 300 at rate of 30 • C /min.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%